The Relationship Between Cigarette Smoke Exposure and Environmental Sanitation with The Incidence of Acute Respiratory Tract Infections in Toddlers - Sayuti; Qotimah; Setyowati, Susana; Rokhamah (Poltekkes Kemenkes Surabaya, 2025)
Acute Respiratory Infections (ARI) constitute infectious pathologies affecting superior or inferior respiratory pathways, capable of producing diverse clinical manifestations ranging from mild infectious processes to severe pathological conditions. Statistical records from the Malang City Health Department documented 56,000 ARI cases over 12 months in 2022, escalating to 43,000 cases within 6 months in 2023, demonstrating significant epidemiological increases. Documentation from TPMB Endang revealed that among 110 toddlers experiencing ARI, 37 originated from Gading Village, with the remaining cases from surrounding communities. Environmental assessment observations identified suboptimal residential hygiene conditions, sugar factory proximity, and prevalent family smoking behaviours. This investigation aimed to establish the relationship between cigarette smoke exposure and environmental sanitation with acute respiratory infection incidence among toddlers in Gading Village, Bululawang District. The research methodology employed quantitative approaches utilising analytical observational design with a cross-sectional framework. The study population encompassed all toddlers residing in Gading Village, totalling 55 individuals, with a sample of 35 toddlers selected according to predetermined inclusion criteria. Multiple linear regression analysis was implemented for data examination. Data analysis results demonstrate significant associations between cigarette smoke exposure and environmental sanitation with acute respiratory tract infection occurrence. This relationship is evidenced through regression variance analysis, specifically the Fh value of 145.846 > Ftable. Additionally, statistical significance is confirmed by the values of 3.178 (cigarette smoke exposure) > t table 1.690 and 2.567 (environmental sanitation) > t table 1.690. The study concludes that definitive relationships exist between cigarette smoke exposure and environmental sanitation with acute respiratory tract infection incidence among toddlers in Gading Village.